2013
DOI: 10.1111/ene.12141
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of brain and vascular imaging including intracranial vessels in transient ischaemic attack patients: external validation of the ABCD3‐I score

Abstract: The inclusion of vascular and neuroimaging information to clinical scales (ABCD3-I score) provides important prognostic information and also helps management decisions, although it cannot give a complete distinction between high-risk and low-risk groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
22
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 29 publications
3
22
0
Order By: Relevance
“…Furthermore, several studies attempting to validate the score's use in emergency care settings have shown inconsistent or discouraging results. [40][41][42] Therefore, although the ABCD2 score may supplement the evaluation of suspected TIA, the utility of this tool in decision making has not been systematically studied and it is not sufficient for triaging patients. Other scores have been more recently developed that may have a better predictive value than the ABCD2 score 43,44 because they include imaging parameters (MRI and vessel imaging) and dual symptoms (ie, similar symptoms in the past week).…”
Section: Triage and Dispositionmentioning
confidence: 99%
“…Furthermore, several studies attempting to validate the score's use in emergency care settings have shown inconsistent or discouraging results. [40][41][42] Therefore, although the ABCD2 score may supplement the evaluation of suspected TIA, the utility of this tool in decision making has not been systematically studied and it is not sufficient for triaging patients. Other scores have been more recently developed that may have a better predictive value than the ABCD2 score 43,44 because they include imaging parameters (MRI and vessel imaging) and dual symptoms (ie, similar symptoms in the past week).…”
Section: Triage and Dispositionmentioning
confidence: 99%
“…Several scores have been derived using retrospective cohorts to predict the early risk of stroke after TIA; the most widely used is the ABCD 2 score. 3,5 Subsequently developed scores have incorporated vascular and parenchymal imaging. 69 Moreover, recent studies have challenged the value of the ABCD 2 score for predicting stroke recurrence risk.…”
mentioning
confidence: 99%
“…Several scores have been derived using retrospective data to predict the early risk of stroke after a TIA (table); the most widely used is the ABCD2 score, with more contemporary scores also including parenchymal and vascular imaging. 12 Incorporating vascular imaging into prediction of stroke after TIA provides the most important information that can be used to alter initial clinical management. The data on risk of recurrent stroke after a minor stroke are more sparse, though it is notable that the Stenting vs Aggressive Medical Management for Preventing Recurrent Stroke in Intracranial Stenosis (SAMMPRIS) trial excluded patients with major disabling strokes.…”
Section: Outcome In Minor Strokementioning
confidence: 99%